Moses the righteous sky gazer - Shoham, Shlomo Giora (Newcastle upon Tyne : Cambridge Scholars Publishing, 2014)
This intellectual biography describes the personal development and Weltanschauung of Moses from his childhood until his death. It includes interactions with well-known biblical and historical figures and with composite characters representing all of the lifestyles that he encountered. It shows how Moses was affected by the people and events in his life and how he was able to lead the Jewish people in their successful struggle for freedom.
A biographical novel about the life and times of Moses.
Print version record.
Added to collection customer.56279.3 - Master record variable field(s) change: 072
Keywords: Moses -- (Biblical leader); Moses -- (Biblical leader); Moses (Biblical leader) -- Meditations; Moses (Biblical leader); Psychology, Religious; Exodus, The; Exodus, The; RELIGION / Biblical Studies / Old Testament; Electronic books